2016
DOI: 10.1186/s12890-016-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

The estimated prevalence of exposure to asthmagens in the Australian workforce, 2014

Abstract: BackgroundThere is very little information available on a national level as to the number of people exposed to specific asthmagens in workplaces.MethodsWe conducted a national telephone survey in Australia to investigate the prevalence of current occupational exposure to 277 asthmagens, assembled into 27 groups. Demographic and current job information were obtained. A web-based tool, OccIDEAS, was used to collect job task information and assign exposure to each asthmagen group.ResultsIn the Australian Workplac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 23 publications
1
28
0
Order By: Relevance
“…OccIDEAS was developed by Fritschi and colleagues and has been used in research studies of carcinogens17 and asthmagens 18. OccIDEAS contains questions relating to usual tasks a worker undertakes.…”
Section: Methodsmentioning
confidence: 99%
“…OccIDEAS was developed by Fritschi and colleagues and has been used in research studies of carcinogens17 and asthmagens 18. OccIDEAS contains questions relating to usual tasks a worker undertakes.…”
Section: Methodsmentioning
confidence: 99%
“…AWES consisted of two cross-sectional telephone surveys conducted among Australian workers to assess the prevalence of current occupational exposure to 38 carcinogens (AWES-Cancer)19 and 27 asthmagen groups (AWES-Asthma),20 respectively. Ethics approval for AWES was obtained from Human Research Ethics Committees of the University of Western Australia and Curtin University.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology for both of the AWES surveys has been described in more detail previously 19 20. In brief, each sample was selected randomly from a list of Australian phone numbers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A multinational study revealed that 26 % of subjects reported exposure to vapours, gas, dust, fumes in their work [4]. As much as 48 % of males and 40 % females could be exposed to one or more asthmagens in their work [5].…”
Section: Introductionmentioning
confidence: 99%